ANALISIS PERBAIKAN KUALITAS GENTENG BETON DENGAN MENGGUNAKAN METODE TAGUCHI - Kailey, Linanda; Wattimanela, Henry J. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2007)
A concrete roof tile company wanted to improve the quality and reduce product defects or rework of products, but companies in the production of concrete roof tile products still fragile because of strong press tiles that are not in accordance with predetermined specifications.To overcome these problems, have made a study to identify factors that influence control of a strong press and concrete roof tiles to get the best settings in producing a product that is expected to perform design of experiments using Taguchi Method to factors that can be controlled by the Cement ( A), water (B), Fly Ash (C) and Dust Stone (D).Each factor had 3 levels of treatment and based on the total number of free degrees in this experiment the orthogonal matrix ( 13 )27 L 3 is used. Based on the results obtained so semenyang largest contribution to the average strength of concrete roof tile press, which is 18.642% of dust and rock that is a combination of 8.167% and the right to obtain a strong tap-concrete roof tiles desired .